Crowdsourcing data interpretation for the response to the first public tsunami alert in the Mediterranean sea, after the October 30th, 2020 earthquake (Mw7.0), Samos, Greece - Katsetsiadou, Katerina-Navsika; Triantafyllou, Ioanna; Papadopoulos, Gerassimos A.; Lekkas, Efthymios; Lozios, Stylianos; Vassilakis, Emmanuel (International Journal of Disaster Risk Reduction, 2023)
On October 30, 2020, 11:51 UTC, a large shallow earthquake of moment magnitude Mw7.0 ruptured the eastern Aegean Sea area and affected several Greek islands, mainly Samos, as well as the Izmir area, western Turkey. A moderate damaging tsunami followed the earthquake and inundated many coastal zones in the area. At 12:15 UTC, the Greek Civil Protection sent to the residents of the eastern Aegean Sea Greek islands a tsunami alert via SMS through the single European emergency phone number 112. It has been the first time that a tsunami warning was publicly issued in the frame of the North-East Atlantic and Mediterranean Tsunami Warning System (NEAMTWS/IOC/UNESCO) since the system became operational during the summer of 2012. Through an on-line questionnaire survey conducted soon after the event we investigated the impact the tsunami 112 alert message had among the population. The aim of this study is to assess the effectiveness of the 112 number as a tool for tsunami early warning, to look after possible weaknesses that may need future improvements and to better understand the level of tsunami risk awareness among the population. The response received from 344 citizens clearly indicates that the particular tsunami alert in general had positive impact to the message recipients, but highlights several weaknesses of the tsunami emergency management chain in Greece and demonstrates some aspects of the 112 system that need improvement.
Keywords: East Aegean sea; European emergency number 112; Public response to alert; Questionnaire survey; Samos 2020 earthquake and tsunami; Tsunami early warning